PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN PERILAKU SUPERVISI KOLABORATIF KEPALA SEKOLAH TERHADAP PERILAKU INOVATIF GURU - , Andarias Mabadi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aimed to examine the effect of transformational leadership style and collaborative supervision behavior towards innovative behavior of teachers. In this study there are two hypotheses proposed, namely: (1) principalâs transformational leadership style has positive influence on innovative behavior of teachers, (2) collaborative supervision has positive influence on innovative behavior of teachers. Method of data collection was conducted using questionnaires. Respondents of this study were all teachers of SMA Negeri 8 Yogyakarta. Analysis tools used in this study is multiple regression analysis. F test and t test used a 5% significance level. The results showed that hypothesis 1 which states that the principalâs transformational leadership style has positive influence on innovative behavior of teachers is accepted. Likewise with the second hypothesis, which states that collaborative supervision behavior of the principal has positive influence on innovative behavior of teachers is accepted. Results of this study concluded that the transformational leadership style and collaborative supervision behavior of the principal has a significant positive effect on the innovative behavior of teachers.